Vitrectomy and All-Cause and Cause-Specific Mortality in Elderly Patients With Vitreoretinal Diseases: A Nationwide Cohort Study - Kim, Yoon Jeon; Lee, Ji Sung; Lee, Yunhan; Lee, Hun; Kim, Jae Yong; Tchah, Hungwon (Frontiers in Medicine, 2022)
Purpose: To determine the all-cause and cause-specific mortality in elderly patients with vitreoretinal diseases based on vitrectomy status. Methods: Elderly patients (aged ≥ 60 years) diagnosed with vitreoretinal diseases between 2003 and 2012 using the Korean National Health Insurance Service-Senior cohort (2002–2015) were included in this nationwide population-based retrospective cohort study. The exposure of interest was vitrectomy, and information on mortality from patient inclusion until December 2015 was obtained. Cox regression modeling was used to assess the association between vitrectomy and mortality. An additional subgroup analysis was performed to investigate the effects of the underlying retinal disease characteristics and comorbidities on mortality. Results: The study cohort included 152,283 patients (3,313 and 148,970 in the vitrectomy and non-vitrectomy groups, respectively). The adjusted model showed vitrectomy was associated with a decreased risk of pulmonary-cause mortality (hazard ratio [HR], 0.51; P < 0.001); however, no association was observed for all-cause mortality (HR, 0.93; P = 0.325). Vitrectomy was associated with increased mortality risk (all-cause: HR, 1.26; P < 0.001 and vascular causes: HR, 1.41; P = 0.003) among patients with retinal vascular diseases and decreased mortality risk (all-cause: HR, 0.64; P < 0.001 and pulmonary causes: HR, 0.35; P = 0.011) among patients with macular diseases. There were significant interactions between age and vitrectomy with respect to all-cause mortality among patients with either vitreoretinal disease. Conclusions: In elderly patients with retinal diseases, the vitrectomy group showed the lower mortality from pulmonary causes with no association for all-cause mortality.